2000
DOI: 10.1002/1531-8249(200009)48:3<372::aid-ana12>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

No tissue damage by chronic deep brain stimulation in Parkinson's disease

Abstract: We report on the pathological findings in the brains of 8 Parkinson's disease patients treated with deep brain stimulation (DBS) of the thalamic ventral intermediate nucleus (6 cases) and subthalamic nucleus (2 cases). DBS was performed continuously for up to 70 months. All brains showed well‐preserved neural parenchyma and only mild gliosis around the lead track compatible with reactive changes due to surgical placement of the electrode. We conclude that chronic DBS does not cause damage to adjacent brain tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
146
1
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(169 citation statements)
references
References 12 publications
19
146
1
3
Order By: Relevance
“…The ED-1 þ immunoreactivity observed correlates to observations of earlier studies that used histochemical techniques and reported large numbers of activated microglia next to chronically implanted stainless steel electrodes placed in cat brain [23]. Several human postmortem studies investigating the tissue reaction to implanted DBS electrodes over indwelling periods from 2 months to several years also have reported activation of microglia/macrophages in the tissue surrounding implanted DBS electrodes, as well as, attached to retrieved DBS electrodes [27][28][29][30][31][32][33][34][35]. Together, the results suggest that activated microglia and macrophages remain adjacent to implanted microwires, as well as other electrode systems, for the life of the implant [36].…”
Section: Discussionsupporting
confidence: 83%
“…The ED-1 þ immunoreactivity observed correlates to observations of earlier studies that used histochemical techniques and reported large numbers of activated microglia next to chronically implanted stainless steel electrodes placed in cat brain [23]. Several human postmortem studies investigating the tissue reaction to implanted DBS electrodes over indwelling periods from 2 months to several years also have reported activation of microglia/macrophages in the tissue surrounding implanted DBS electrodes, as well as, attached to retrieved DBS electrodes [27][28][29][30][31][32][33][34][35]. Together, the results suggest that activated microglia and macrophages remain adjacent to implanted microwires, as well as other electrode systems, for the life of the implant [36].…”
Section: Discussionsupporting
confidence: 83%
“…In general, our data supports the results of previous post-mortem studies, which have shown that a glial response (e.g. mild inflammation) is consistently generated to DBS leads (Sun et al 2008;Nielsen et al 2007;Haberler et al 2000;Henderson et al 2002). Interestingly we were able to observe a few cases of peri-lead inflammatory cuffing, as well as cortical and peri-lead hemorrhage/stroke.…”
Section: Discussionsupporting
confidence: 92%
“…Previous PM studies have not usually demonstrated pathological changes adjacent to the DBS lead [6,12] and all concluded that DBS does not cause damage to the neuroparenchymal tissue, regardless of the period of stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the gold standard for definitive verification of the anatomical location of the electrodes is at post-mortem (PM) histological work-up. In the published literature, there are only seven such reports [3,6,8,10,13,16,18]. MER was used in five of these, while MRI guidance, clinical testing, and image verification was used in two [8,13].…”
Section: Introductionmentioning
confidence: 99%